Suppression of dust pollution by double-network material based on enzymatic calcification. (20th December 2021) - Sun, Xiaohao; Miao, Linchang; Wang, Hengxing; Yuan, Junhao; Fan, Guangcai; Xia, Jingxin
Highlights: The EC-PVAc is effective to suppress dust generation and improve shear resistance. A lower PVAc concentration is enough to improve wind-erosion resistance. EC-PVAc (50 g/L) treatment is more suitable to solidify dust soils in field tests. Abstract: Globally, most cities are facing the severe challenge of dust pollution. Therefore, it is of great significance to find an effective and environmentally friendly method for the suppression of dust generation. This study combined enzymatic calcification with polyvinyl acetate (EC-PVAc) treatment for dust control. To identify the optimal treatment condition for practical field application, wind tunnel tests and direct shear tests were performed. The feasibility of EC-PVAc treatment for the suppression of dust generation was demonstrated with a field test. The results showed that with increased PVAc concentration, both wind-erosion resistance and shear resistance of treated dust soils improved. With combined EC-PVAc treatment with 50 g/L PVAc, the treated dust soils showed a stable and cost-efficient double-network structure. Therefore, EC-PVAc (50 g/L) treatment was applied to solidify dust soils in the subsequent field test. In response to the treatment, vehicles passing the test site generated significantly lower concentrations of PM2.5 and PM10 at the field test site, especially near the soil surface. With EC-PVAc (50 g/L) treatment, the treated field test site had higher surface strength than an untreated area. These results demonstrate that EC-PVAc treatment significantly suppressed dust generation and improved shear resistance, which presents promising potential for the prevention of dust pollution.